SOCIAL NETWORK SERVICES INFLUENCE KNOWLEDGE SHARING AMONG RESEARCHERS BETWEEN THREE UNIVERSITIES IN IRAQ - Ibrahim, Hassan M.; Shyaa, Methaq A.; Hasan, Ayat Saleh; Mohd, Othman; Zakaria, Nurul Azma (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge sharing is the process of transferring skills and experience that has been gained through learning and experience between the people. Sharing of knowledge led to the creation of new knowledge and provides the appropriate atmosphere to enable researchers can improve the quality of research, and to reduce the cost and time. Generally, Iraq Universities have experienced a few problems that lead to a reduction in the sharing of knowledge. Therefore, this study contributes to find solutions for sharing knowledge with the review of factors that affect the Knowledge exchange within the higher education sector of Iraq. The result of this study is to improve the level of knowledge sharing between researchers and staff of the higher education sector.